2002
DOI: 10.1007/s00586-002-0455-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of intervertebral disc tissue on anterior spinal interbody fusion: an experimental study on pigs

Abstract: Intervertebral disc has been shown to be related to low back pain and nerve root injury in pathologic conditions. However, little is known about its influence on spinal fusion. With the development of minimal invasive operations, such as laparoscopic anterior spinal fusion with cages, insufficient discectomy may occur. With its inflammatory properties, the residue nucleus pulposus may have an effect on spinal fusion. In this study, a two-level lumbar spine interbody fusion (L3/4, L5/6) with a Brantigan cage wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 17 publications
1
29
0
4
Order By: Relevance
“…Inadequate removal of disc material and vertebral body endplate cartilage increases the risk of pseudarthrosis. Li et al [9] showed that nucleus pulposis mixed with bone graft slows down the rate of bony growth, possibly through inflammatory mediators. Lowe et al [10] asserted that total area of discectomy and endplate preparation play a role in fusion rate.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate removal of disc material and vertebral body endplate cartilage increases the risk of pseudarthrosis. Li et al [9] showed that nucleus pulposis mixed with bone graft slows down the rate of bony growth, possibly through inflammatory mediators. Lowe et al [10] asserted that total area of discectomy and endplate preparation play a role in fusion rate.…”
Section: Introductionmentioning
confidence: 99%
“…A porcine model of three-level lumbar interbody fusion was employed in this study. The porcine model was described in our previous studies and had been shown to be a feasible model when human implants are to be engaged [12,29]. In the present experiment, the pigs had a mean serum platelet concentration of 398,400/µl, which is slightly higher than that among humans.…”
Section: Discussionmentioning
confidence: 58%
“…An early effect of the PRP was therefore expected at the start of the experiment, and the observation time was set at 3 months, during which a reasonable fusion rate for autograft levels has been observed in our previous study [12]. Based on the later histomorphometric evaluation, there remain about 14% unabsorbed β-TCP granules.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The lumbar spine fusion model was first built in pigs (Figure 2), which has a reported fusion rate close to that of humans [87,88]. Spinal fusion was evaluated by radiography, micro-CT and histomorphometry, and they concluded that BPE achieved the same fusion rate and the same percentage of new bone formation as that of an autologous iliac bone graft in this demanding porcine anterior spinal fusion model after 12 weeks (Figures 3 and 4) [45,78,89].…”
Section: Spinal Fusionmentioning
confidence: 89%